2021
DOI: 10.1128/spectrum.00389-21
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome of the Successful Freshwater Invader, the Signal Crayfish, and Its Changes along the Invasion Range

Abstract: Invasive species are among the major drivers of biodiversity loss and impairment of ecosystem services worldwide, but our understanding of their invasion success and dynamics still has many gaps. For instance, although it is known that host-associated microbial communities may significantly affect an individual’s health and fitness, the current studies on invasive species are mainly focused on pathogenic microbes, while the effects of the remaining majority of microbial communities on the invasion process are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 91 publications
2
13
0
Order By: Relevance
“…In this study, potential bacterial causative agents were examined by comparing the bacterial composition of hepatopancreas between the individuals exhibiting mild and moderate histopathology. Multiple studies have recorded bacteria in hepatopancreas of crustaceans (Cheung et al, 2015;Dragičević et al, 2021b;Wu et al, 2021;Zhang et al, 2020). Additionally, some studies (Dragičević et al, 2021b;Zhang et al, 2020) found similarities between bacterial communities of hepatopancreas and other tissues, suggesting that bacteria are shared between tissues and that tissues of healthy crustaceans are not sterile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, potential bacterial causative agents were examined by comparing the bacterial composition of hepatopancreas between the individuals exhibiting mild and moderate histopathology. Multiple studies have recorded bacteria in hepatopancreas of crustaceans (Cheung et al, 2015;Dragičević et al, 2021b;Wu et al, 2021;Zhang et al, 2020). Additionally, some studies (Dragičević et al, 2021b;Zhang et al, 2020) found similarities between bacterial communities of hepatopancreas and other tissues, suggesting that bacteria are shared between tissues and that tissues of healthy crustaceans are not sterile.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have recorded bacteria in hepatopancreas of crustaceans (Cheung et al, 2015;Dragičević et al, 2021b;Wu et al, 2021;Zhang et al, 2020). Additionally, some studies (Dragičević et al, 2021b;Zhang et al, 2020) found similarities between bacterial communities of hepatopancreas and other tissues, suggesting that bacteria are shared between tissues and that tissues of healthy crustaceans are not sterile. Due to high abundance of bacteria from order Rickettsiales and class Mollicutes which also includes highly abundant genus Candidatus Hepatoplasma, their role in health and immunity of crustaceans needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed significant differences in immune response between the upstream and downstream signal crayfish populations might be due to differences in microhabitat characteristics. The approximately 33 km-long invasion range of the signal crayfish in the Korana River consists of microhabitats which differ in temperature, surrounding vegetation, water depth, sediment type, and anthropogenic pressure, with the upstream part of the Korana River flowing through the sparsely populated rural region, and the downstream part of the invasion range located in the industrial zone of the Karlovac City [ 104 ]. Additionally, it has been previously reported that different environmental parameters (e.g., temperature, pollution, oxygen levels, pH, and salinity) may affect crayfish immune system/health status [ 93 , 105 , 106 , 107 , 108 , 109 , 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated that bacterial microbiomes can have pivotal roles in invasion ecology. In signal crayfish, the intestinal microbial communities may affect and be affected by range expansion [14]. A survey of Cambarus sciotensis showed that the microbial diversity and composition of carapace and gills are determined by interactions within the local environment and host microsites [15].…”
Section: Introductionmentioning
confidence: 99%